Clustered chain founded on ant colony optimization energy efficient routing scheme for under-water wireless sensor networks - Djilali Moussaoui; Mourad Hadjila; Sidi Mohammed Hadj Irid; Sihem Souiki (International Journal of Electrical and Computer Engineering (IJECE), 2021)
One challenge in under-water wireless sensor networks (UWSN) is to find ways to improve the life duration of networks, since it is difficult to replace or recharge batteries in sensors by the solar energy. Thus, designing an energy-efficient protocol remains as a critical task. Many cluster-based routing protocols have been suggested with the goal of reducing overall energy consumption through data aggregation and balancing energy through cluster-head rotation. However, the majority of current protocols are concerned with load balancing within each cluster. In this paper we propose a clustered chain-based energy efficient routing algorithm called CCRA that can combine fuzzy c-means (FCM) and ant colony optimization (ACO) create and manage the data transmission in the network. Our analysis and results of simulations show a better energy management in the network.